Factors That Influence the Desire of Nursing Students of The Ministry of Health Poltekkes Semarang in the Mental Health Counseling Guidance Process - Dela Savitri Dwi Astuti; Sri Endang Windiarti; Wien Soelistyo Adi (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Student mental health is an important issue in higher education, yet many students remain reluctant to utilize counseling services. Several factors are suspected to influence students’ willingness to participate in counseling, including stress levels, social support, public stigma, and self-stigma. This study aimed to determine the relationship between stress level, social support, public stigma, and self-stigma with students’ intention to engage in mental health counseling. The research used a quantitative design with a cross-sectional approach. A total of 202 first-year nursing students from Campus I of Poltekkes Kemenkes Semarang were selected using a total sampling technique. The research instrument was a questionnaire that had been tested for validity and reliability, and data were analyzed using Spearman’s rho correlation test. The results showed that most students had a moderate level of stress (52.8%), adequate social support (58.1%), moderate public stigma (53.7%), and moderate self-stigma (55.3%). Students’ willingness to seek counseling was also in the moderate category (63.4%). Statistical analysis indicated a significant relationship between stress level (p=0.000), social support (p=0.002), public stigma (p=0.000), and self-stigma (p=0.000) with the intention to engage in mental health counseling. These findings highlight the importance of promotive and preventive approaches from educational institutions to enhance students’ awareness and access to mental health counseling services.